Improving the process of control and correction of errors in non-positional code structures - Yanko, Alina; Krasnobayev, Victor; Hlushko, Alina (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the processes of operational control and correction of data errors in non-positional code structures (NCS). Based on a critical analysis of the existing data control method based on the use of the projection of a number in RCS, limited control efficiency and the ability to detect only single errors have been established. The study improves methods for rapid control and data correction of a real-time computer system (CS) operating in a non-positional number system, in the so-called residual class system (RCS). A comprehensive approach to control and eliminate errors in RCS is built on the basis of non-positional coding, underlying which is the Chinese residual theorem. This theorem proves that NSC is the next stage in the development of the theory of information control using arithmetic control by modulus. The use of the property of complete arithmetic of NSC has made it possible to improve the method and increase the efficiency of data control due to information processing in RCS without controlling each intermediate result obtained. Comparison with the most efficient existing method has made it possible to establish that the devised method provides an increase in the speed of data control by 1.2–1.3 times. An effective process of operational and accurate error detection based on an improved method of data control in RCS, which is based on the use of the corrective properties of NCS, has been proposed. Parallel error correction in NCS increases the efficiency of error correction by 2 times, due to a decrease in the number of intermediate operations in the improved method. At the same time, with an increase in the bit grid of the operands being processed, the efficiency of the application of the considered error correction process improves